TEKNOLOGI ALAT TANGKAP BUBU LIPAT RAMAH LINGKUNGAN BAGI NELAYAN DI DESA LANTEBUNG KOTA MAKASSAR (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The trap used by the Lantebung community to catch crabs is a type of folding trap that is triangular with a frame made of iron and can be folded.  The problem with using this trap is that it often catches small crabs (the carapace width
Keywords: Folding trap; escape gap; blue swimming crab; Lantebung village